Effects of anthropogenic climate change on the potential distribution of the genus Pronophila Doubleday, [1849] in Colombia (Lepidoptera: Satyrinae, Pronophilina) - Murillo-P., Ana María; Mahecha-J., Oscar; Díaz-S., Vanessa; Andrade-C., Miguel Gonzalo; Pyrcz, Tomasz W. (SHILAP Revista de lepidopterología, 2024)
The Pronophila Doubleday, [1849] genus, belonging to the Pronophilina subtribe (Nymphalidae: Satyrinae), is distributed from northwest Argentina to the extreme north of Colombia and northeast Venezuela, with only one representative in Central America. However, much about the natural history of the genus is still unknown. Additionally, anthropogenic disturbances have caused accelerated climate change, affecting different taxa’sdistribution and diversity patterns, including species of the Pronophila genus in Colombia due to the Andean region being one of the most affected areas by such activities in recent decades. Therefore, this study aimed to generate a potential distribution model for Pronophila species in the country under various climate change scenarios for the years 2050 and 2070. A comparison was also made with a recent potential distribution model to evaluate the effect of climate change on the genus’ distribution in the country. The R software was used with the MaxEnt algorithm to project different models. The results showed that the four Pronophila species used in the modeling experienced reductions in their potential ranges in the years 2050 and 2070. Lastly, the study’s results can be used to develop conservation strategies that mitigate population declines and local extinctions of Lepidoptera associated with the mountainous ecosystems of the country.